Impact of WhatsApp on the Vocabulary Acquisition of Secondary School Students in Ogbomoso, Oyo State, Nigeria - Abdulmalik Abiola Salman; Muhyideen Olasunkanmi Imam (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
The advent of technology has brought a change in the dynamics of second language teaching and learning. WhatsApp has been a common tool used among students for communicating and chatting with friends, peers, and relatives. Its commonality may be because of its easy installation as mobile application on mobile devices. Educators are beginning to explore its potentials toward seeing how it can help students in their learning. Since it is apparently a novel tool in the education sector, its usefulness in acquiring vocabulary by secondary school students is yet to be ascertained. Therefore, this study examined the impact of WhatsApp on vocabulary acquisition of secondary school students in Ogbomoso, Oyo State, Nigeria. This study was premised on the constructivist learning theory since WhatsApp provides students the opportunity to construct their vocabulary knowledge. The sample for the study comprised 250 students from five secondary schools randomly selected in Ogbomoso, Oyo State. Data for the study were generated from the participants using self-made questionnaire. The questionnaire is structured into 5 points from Strongly Agree to Strongly Disagree. Mean and standard deviation were employed to analyse the data. Findings showed that more than half of the students believe WhatsApp is expedient in learning and acquiring vocabulary. It further revealed that the majority of the students perceive WhatsApp as an effective social network that enhances their vocabulary acquisition as it is easy to acquire new words and understand their meanings through WhatsApp. The study concluded that language teachers should devise means of adopting social media such as WhatsApp to teach their students since students are favourably disposed to learning through WhatsApp.